2011
DOI: 10.1002/asi.21682
|View full text |Cite
|
Sign up to set email alerts
|

Citation flows in the zones of influence of scientific collaborations

Abstract: Domestic citation to papers from the same country and the greater citation impact of documents involving international collaboration are two phenomena that have been extensively studied and contrasted. Here, however, we show that it is not so much a national bias, but that papers have a greater impact on their immediate environments, an impact that is diluted as that environment grows. For this reason, the greatest biases are observed in countries with a limited production. Papers that involve international co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 20 publications
5
43
0
2
Order By: Relevance
“…It is a noteworthy finding that the Knowledge Management Model designed for internal collaboration also had a positive impact on external collaboration. This is a valuable result for the University because the returns on international collaboration are high (Lancho Barrantes et al 2012;Ynalvez and Shrum 2011).…”
Section: Findings With Implications For the Universitymentioning
confidence: 99%
See 1 more Smart Citation
“…It is a noteworthy finding that the Knowledge Management Model designed for internal collaboration also had a positive impact on external collaboration. This is a valuable result for the University because the returns on international collaboration are high (Lancho Barrantes et al 2012;Ynalvez and Shrum 2011).…”
Section: Findings With Implications For the Universitymentioning
confidence: 99%
“…Since then, scientometric studies have shown that, depending on the scientific discipline and other factors, research collaboration can have a positive relationship with number of publications (Abramo et al 2009;Lee and Bozeman 2005) as well as number of citations (Abramo et al 2017;Lancho-Barrantes et al 2012), and collaboration has become a priority in research management around the globe. Because of the relationship between collaboration, publications, and citations, universities are looking for ways to increase collaboration.…”
Section: Introductionmentioning
confidence: 99%
“…Their analysis of the collaborations between countries revealed that six countries (United States, United Kingdom, Germany, France, Italy, and Canada) account for 82 % of the world's international publications, but they are not the most collaborative countries, if measured by their proportion of collaborative output. On the other hand, Lancho-Barrantes et al (2012) explored the provenance of the citations received by the different countries and the different types of collaborative papers. They found different percentages of papers in collaboration among countries.…”
Section: Introductionmentioning
confidence: 99%
“…As in previous studies (Lancho-Barrantes et al 2012;Chinchilla-Rodríguez et al 2012) the results of our research may also give some recommendations for better publication and collaboration practice in a given department or research institution by encouraging publishing in journals with higher visibility and greater impact in the international scientific community. That in turn entails attracting more international partners and incentivising international collaboration with institutions abroad.…”
Section: Discussionmentioning
confidence: 79%